A secure mobile group buying system based on the concept of spontaneity. Issue 7 (3rd October 2016) - Chen, Chin-Ling; Deng, Yong-Yuan
Abstract : Purpose: The purpose of this paper is to propose a secure mobile group-buying system for application on spontaneous group-buying websites. Design/methodology/approach: The proposed mechanism uses the Schnorr digital signature technique. Findings: The proposed scheme is able to satisfy many security requirements. The computation costs of each phase and party were also analyzed, and the communication cost of each phase was calculated. Originality/value: The results indicate that the proposed scheme is suitable for real-world application.